DNA ploidy in bronchopulmonary carcinoid tumours. Issue 3 (March 1988) - Jones, D J; Hasleton, P S; Moore, M
Abstract : Fifty three bronchopulmonary carcinoid tumours were studied to assess the significance of DNA ploidy, determined by flow cytometry of paraffin embedded tissue. Twenty eight were typical carcinoid tumours and 25 well differentiated neuroendocrine carcinomas. Twenty seven were DNA diploid and 26 DNA aneuploid. DNA aneuploidy was significantly associated with histological features of increased malignant potential. Survival data were available for 43 patients. Of the 19 with DNA diploid tumours, 16 survived five years, compared with 14 of 24 with DNA aneuploid tumours–the difference being at the borderline of statistical significance. In a Cox multivariate regression analysis with other histological variables, DNA ploidy did not confer independent prognostic information. It is concluded that, although DNA aneuploidy as determined by flow cytometry is an indicator of increased malignant potential in bronchopulmonary carcinoid tumours, it does not provide clinically useful information additional to the results of routine histological examination.